Concept Analysis of Resilience in Adolescent Living with HIV: Review of Limitations and Implications - Astiti, Indita Wilujeng; Yosep, Iyus; Hernawaty, Taty (JURNAL INFO KESEHATAN, 2024)
Resilience is characterized by ‘the ability to bounce back from challenge and adversity’. However, being Adolescent Living with HIV (ALHIV) give larger challenges on an individual throughout their life because of their characteristic and illness. After all, positive results such as resilience are also feasible, yet knowledge on resilience in ALHIV remains limited and resilience assessment methods continue to be debated and need further clarification of the concept of resilience is needed about this population. In recent years, empirical research on resilience has grown, criticism have been mostly concentrates on ambiguity definition and implications. This concept analysis aims to identify the concept of the resilience ALHIV by identifying the attributes that determine the concept, antecedents and consequences. This study tries to discover the traits that determine the concept of resilience in ALHIV using Walker and Avant’s approach, with searches performed in the CINAHL, PubMed, Science Direct and PsycInfo. The results of the analysis reveal the resilience antecedents of ALHIV such as coping strategy, illness acceptance, positive adaptation, self-efficacy, positive future expectation, emotional regulation, family support, school connectedness and healthcare support. The consequences of the concept of resilience in ALHIV include positive outcomes include improved adherence to treatment, psychological well-being, positive coping strategy, better school performance and positive social relationship.